Outcomes of corneal transplantation in Europe: report by the European Cornea and Cell Transplantation Registry. Issue 6 (June 2021) - Dunker, Suryan L.; Armitage, W. John; Armitage, Margareta; Brocato, Lucia; Figueiredo, Francisco C.; Heemskerk, Martin B.A.; Hjortdal, Jesper; Jones, Gary L.A.; Konijn, Cynthia; Nuijts, Rudy M.M.A.; Lundström, Mats; Dickman, Mor M.
Abstract : This report by the European Cornea and Cell Transplantation Registry provides real-world estimates of graft survival and visual acuity in a cohort of 12 913 corneal transplants. Abstract : Purpose: To analyze real-world graft survival and visual acuity outcomes of corneal transplantation in Europe. Setting: Corneal clinics in 10 European Union member states, the United Kingdom, and Switzerland. Design: Multinational registry study. Methods: All corneal transplant procedures registered in the European Cornea and Cell Transplantation Registry (ECCTR) were identified. Graft survival of primary corneal transplants were analyzed using Kaplan-Meier survival curves with log-rank test and Cox regression. Corrected distance visual acuities (CDVAs) are reported at baseline and 2 years postoperatively using the Lundström distribution matrix. Results: A total of 12 913 corneal transplants were identified. Overall, 32-year graft survival of corneal transplants was high (89%) but differed between indications, ranging from 98% in keratoconus and 80% for trauma. Overall, CDVA improved postoperatively, but the risk for losing vision ranged from 7% (baseline vision ≤0.1 Snellen) to 58% (baseline vision ≥1.0 Snellen). Conclusions: This report provides a comprehensive overview of graft survival and visual outcomes of corneal transplantation in Europe. In addition, it provides real-world estimates of outcomes for a variety of indications and surgical techniques to support benchmarking and demonstrates the relationship between baseline and postoperative vision.